Role of extracellular adenosine in Drosophila - Fencková, Michaela (Jihočeská univerzita, 2012)
This thesis describes several aspects of the role for extracellular adenosine in Drosophila. Reverse genetic, molecular and microscopic methods together with the most forefront Drosophila research techniques have been applied to elucidate the role of adenosine signaling in the regulation of development, physiology and metabolism of Drosophila larvae. The thesis helps to establish the model for extracellular adenosine as a stress-signal for the release of energy stores. It also describes the elucidation of Drosophila extracellular adenosine production pathway by functional characterization of extracellular ATP/adenosine converting enzymes. Further, this thesis describes the attempt to study adenosine signaling by creation of tissue specific knock-down mutation of Drosophila adenosine receptor. Finally, it provides results of the utilization of in vivo fluorescent reporters for studying of the localization, function and interaction of enzymes implicated in adenosine signaling pathway.
Role of extracellular adenosine in Drosophila
Keywords: adenosine; drosophila; glucose metabolism; ekto-5'-nucleotidases; in vivo reporters; adenosine; drosophila; glucose metabolism; ekto-5'-nucleotidases; in vivo reporters